45.8k views
23 votes
Solve the following equation:
2(-2x -4) + 6 = 5 - 3(x+1)
HELP ME PLEASE

User Lighthart
by
5.1k points

1 Answer

6 votes

Answer:

x = -4

Explanation:

2(-2x - 4) + 6 = 5 - 3(x+1)

Distribute the numbers outside the parenthesis to the numbers inside the parenthesis. You should have this equation:

-4x - 8 + 6 = 5 - 3x -3

Combine like terms:

-4x - 2 = 2 - 3x

Add a positive 3x to both sides to have the variable x on one side only.

-4x - 2 = 2 - 3x

+3x +3x

-x - 2 = 2

Add two to both sides to isolate the variable, x.

-x - 2 = 2

+2 +2

-x = 4

Divide both sides by -1 to leave x by itself.

-x = 4

-1 -1

x = -4

The final answer should be x = -4.

User Prima
by
5.3k points